(untitled) (Indian Journal of Arid Horticulture, 2013)
Brinjal has been a stable vegetable in our diet since ancient time and being grown in all cropping seasons round the year. It has several vernacular names viz., egg plant, aubergine, baingan badone, kausi, vangi, vazhuthana (Yawalkar, 1985). Brinjal is highly productive and usually find its place as the poor man’s crop. It is rich source of minerals (calcium, magnesium, phosphorus, sodium, potassium, chlorine, iron etc.), vitamins and also has some medicinal importance (Choudhary, 1967). In production and productivity, India stands second in the world after China. The total area under cultivation of this crop in our country is 6.12 lack hectares with an annual production of 105.63 lack tones with a productivity of 17.3 Mt / ha. In Rajasthan, it is grown in an area of 5560 hectare with an annual production of 0.22 lack tones with a 3.941 Mt/ ha productivity (Anonymous, 2010). It is generally grown in all districts of Rajasthan during summer and rainy seasons. The brinjal crop is attacked by a number of insect pests right from germination to harvesting, namely, jassids, Amrasca biguttula biguttula (Ishida); whitefly, Bemisia tabaci (Genn.); aphid, Aphis gossypii Glover; lace wing bug, Urentius sentis Distant; Hadda beetal, Henosepilachna vigintioctopunctata (Fab.), shoot and fruit borer, Leucinodes orbonalis Guen.; and stem borer, Euzophera perticellaRag.